Érték és szabadság Felelősségünk a szerzői jog dinamikus egyensúlyának alakításában - Pogácsás Anett (IUSTUM AEQUUM SALUTARE, 2016)
“To my mind, copyright ought to be about liberating us from ignorance, enriching our culture and therefore the idea of copyright and freedom existing side by side as partners is a natural fit not an aberration” – we have to agree with these words of Brian Fitzgerald. This study points out that it is our responsibility to achieve this ambition in practice, in all the areas covered by copyright law. As János Zlinszky stressed, it is our calling to make our own efforts with the toolbar of our profession and stand where infringement is observed. Accordingly, the European Commission emphasizes that we need to promote innovation for the benefit of consumers, service providers and right holders in the same time, where both the freedom to provide and to receive services shall be ensured. To achieve this aim copyright is an important tool: we cannot forget that although not only on copyright law stands or falls the matter of culture, but it has a great role in it, so our responsibility is enormous for shaping the dynamic balance of copyright.